Some Operator Inequalities on Chaotic Order and Monotonicity of Related Operator Function - Changsen Yang; Yanmin Liu (Abstract and Applied Analysis)
We will discuss some operator inequalities on chaotic order about several operators, which are generalization of Furuta inequality and show monotonicity of related Furuta type operator function.